Fractional Order Level Control of a System with Communicating Vessels - Copot, Cosmin; Ionescu, Clara M.; Keyser, Robin De (Journal of Applied Nonlinear Dynamics, 2026)
This paper illustrates the advantages and disadvantages of using integer- and fractional-order control algorithms for an example of a system with S-shape dynamics. A laboratory setup of communicating vessels, where the level is regulated by means of a pump, is described. Both PI and PID control are designed, im- plemented and tested on the real setup. The results show that fractional order control may outperform classical PID control, under specific conditions.